THE RESULTS OF A CLINICAL EVALUATION OF THE USE OF STROMAL VASCULAR FRACTION, BONE MARROW CONCENTRATE FOR THE TREATMENT OF OSTEOARTHRITIS OF THE KNEE JOINT IN THE EARLY STAGES - Maxsur M. Abdullaev ,; Saodat U. Asilova ,; Abduaziz Sh. Babakulov ,; Khurshid A. Abdusattorov ,; Vosit X. Tursunov ,; Akbar B. Mirzayev ,; Kholbek E. Aliyev, (Central Asian Journal of Medicine, 2025)
The aim of the study is to investigate the combined use of high-potency fatty tissue stem cells with platelet-rich plasma in patients to reduce the development of knee osteoarthritis. The results were evaluated using clinical methods. The views of modern scholars on this matter are presented. The results have been presented, discussed, and recommended for use in knee osteoarthritis.